Cyclosporin A induces cardiac differentiation but inhibits hemato-endothelial differentiation of P19 cells. - Seung-Cheol Choi; Hyunjoo Lee; Ji-Hyun Choi; Jong-Ho Kim; Chi-Yeon Park; Hyung-Joon Joo; Jae-Hyoung Park; Soon-Jun Hong; Cheol-Woong Yu; Do-Sun Lim (PLoS ONE)
Little is known about the mechanisms underlying the effects of Cyclosporin A (CsA) on the fate of stem cells, including cardiomyogenic differentiation. Therefore, we investigated the effects and the molecular mechanisms behind the actions of CsA on cell lineage determination of P19 cells. CsA induced cardiomyocyte-specific differentiation of P19 cells, with the highest efficiency at a concentration of 0.32 μM during embryoid body (EB) formation via activation of the Wnt signaling pathway molecules, Wnt3a, Wnt5a, and Wnt8a, and the cardiac mesoderm markers, Mixl1, Mesp1, and Mesp2. Interestingly, cotreatment of P19 cells with CsA plus dimethyl sulfoxide (DMSO) during EB formation significantly increases cardiac differentiation. In contrast, mRNA expression levels of hematopoietic and endothelial lineage markers, including Flk1 and Er71, were severely reduced in CsA-treated P19 cells. Furthermore, expression of Flk1 protein and the percentage of Flk1+ cells were severely reduced in 0.32 μM CsA-treated P19 cells compared to control cells. CsA significantly modulated mRNA expression levels of the cell cycle molecules, p53 and Cyclins D1, D2, and E2 in P19 cells during EB formation. Moreover, CsA significantly increased cell death and reduced cell number in P19 cells during EB formation. These results demonstrate that CsA induces cardiac differentiation but inhibits hemato-endothelial differentiation via activation of the Wnt signaling pathway, followed by modulation of cell lineage-determining genes in P19 cells during EB formation.